Local economies, local wealth, and economic perceptions - Ansell, B; Cansunar, A (2022)
Recent research in political economy has demonstrated that local economic conditions have a striking impact on the evaluation of the incumbent, social policy preferences, and support for anti-establishment movements. Whether voters can correctly perceive their district's economic reality and the origins of these perceptions, however, have not received much attention from scholars. This article develops a theoretical argument linking the local economy and household affluence to perceptions. We theoretically argue and empirically demonstrate that, in evaluating the local economy, richer and economically more secure individuals see the world through rose-colored glasses, often misperceiving actual local economic conditions. Drawing upon data from the British Election Survey and local authority level economic indicators, we show that negative subjective perceptions strongly predict support for Brexit, disapproval of the government, and demand for redistribution.